Primary resistance to clarithromycin, metronidazole and amoxicillin of Helicobacter pylori isolated from Tunisian patients with peptic ulcers and gastritis: a prospective multicentre study - Ben Mansour Khansa; Burucoa Christophe; Zribi Meriem; Masmoudi Afef; Karoui Sami; Kallel Lamia; Chouaib Soufiène; Matri Samira; Fekih Monia; Zarrouk Sonia; Labbene Mounir; Boubaker Jalel; et al. (BMC, 2010)
Abstract Background The frequency of primary resistance to antibiotics in H. pylori isolates is increasing worldwide. In Tunisia, there are limited data regarding the pattern of H. pylori antibiotic primary resistance. Aim To evaluate the primary resistance of H. pylori to clarithromycin, metronidazole and amoxicillin and to detect the mutations involved in clarithromycin resistance. Materials and methods 273 strains isolated from adults and children were enrolled. The primary resistance to clarithromycin, metronidazole and amoxicillin was evaluated by means of E-test minimal inhibitory concentration (MIC). The real-time PCR using Scorpion primers was performed in all cases to assess clarithromycin primary resistance and point mutations involved. Results No resistance to amoxicillin was detected. For adults, resistance to clarithromycin and metronidazole was found respectively in 14.6% and 56.8%, and respectively in 18.8% and 25% in children. Overall, the rates of global primary resistance to clarithromycin and metronidazole in Tunisia were respectively determined in 15.4% and 51.3%. By the use of Scorpion PCR, the A2143G was the most frequent point mutation observed (88.1%), followed by the A2142G (11.9%); the A2142C was not found and 18 of 42 patients (42.8%) were infected by both the resistant and the susceptible genotype. The association of clarithromycin resistance with gender was not statistically significant, but metronidazole resistant strains were isolated more frequently in females (67.8%) than in males (32.2%) and the difference was significant. As for gastroduodenal diseases, the difference between strains isolated from patients with peptic ulceration and those with non peptic ulceration was not statistically significant. When about the distribution of resistant strains to clarithromycin and metronidazole between the three Tunisian cities (Tunis, Menzel Bourguiba and Mahdia), the difference was not statistically significant. Conclusion Local data regarding the primary resistance of H. pylori to clarithromycin, metronidazole and amoxicillin and the main genetic mutation involved in clarithromycin resistance in vivo (A2143G) are necessary to prove a clear need for a periodic evaluation of antibiotic consumption and new therapeutic strategies in Tunisia in order to avoid the emergence of resistant strains.